The Mediation Role of Innovation Capability and Green Innovation Strategy on Sustainable Leadership-Sustainability Performance Relationship: Studi at a Class C Private Hospital In Surabaya Raya, East Java - Purwanto, Marini; Ellitan, Lena (Program MM Universitas Surabaya, 2026)
Purpose: The aim of this research is to examine the influence of sustainable leadership on sustainable performance with the mediating effect of innovation capability and green innovation strategy at Class C Private Hospitals in Surabaya, East Java. Method: This research is quantitative in nature and was conducted using survey research. A questionnaire was used to collect data from 61 hospitals in Surabaya Raya , East Java, using a five-point Likert scale. All hypothesized relationships were tested using partial least partial structural equation modeling (PLS-SEM). Result: Empirical results show that comprehensive implementation of green innovation strategy significantly improves sustainability performance including economic, environmental and social performance. In addition, green innovation strategy partially mediates the influence between sustainability performance and sustainability performance significantly and positively. However, innovation capability was not proven to mediate the influence of sustainable leadership on sustainability performance.